The Political Consequences of Green Policies: Evidence from Italy - Italo Colantone; Livio Di Lonardo; Yotam Margalit; Marco Percoco (Center for Economic Studies and ifo Institute (CESifo), 2022)
For many governments enacting green policies is a priority, but these often entail substantial and uneven costs on citizens. How does the introduction of green policies affect voting? We study this question in the context of a major ban on polluting cars introduced in Milan. The policy was strongly opposed by the right-wing populist party Lega, portraying it as a "radical-chic-leftist" initiative penalizing common people. We show that owners of banned vehicles—who incurred a median loss of exteuro3,750—were significantly more likely to vote for Lega in the subsequent elections. This electoral shift does not stem from increased environmental skepticism, but rather from the perceived unfairness of the policy and its pocketbook implications. In fact, recipients of compensation from the local government were not more likely to switch to Lega. The findings underscore that addressing the distributive consequences is key for advancing green policies that are politically sustainable.
Keywords: P10; D70; Q50; 330; environmental politics; green policies; distributional consequences; compensation mechanisms